Considering the role of behaviors in sustainability and climate change education - Eilam, Efrat (Frontiers in Psychology, 2025)
At the heart of sustainability and climate change education discourse is the notion of student behavioral change, as an emphasized goal. The central positioning of behavior modification raises moral and ethical concerns, as well as concerns regarding the impacts on student well-being. In addressing these issues, this conceptual paper interrogates the role ascribed to student behavior in sustainability education and climate change education. Multiple lenses are applied to critique the behavioral modification approach. Finally, it is proposed to reframe the role of behavior and to conceptualize behavior as forming part of ethics education, where the focus shifts from assigning behavior an instrumental role to conceptualizing its intrinsic educational value.